The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/su12010409
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility Information Disclosure and Innovation Sustainability: Evidence from China

Abstract: We selected the Chinese A-share listed companies during period of 2007 to 2017 as the research subject, and from the perspective of information and reputation effects, we examined the relationship between corporate social responsibility (CSR) information disclosure and innovation sustainability. The results show that CSR information disclosure has a significant positive relationship with innovation sustainability. Analysis of the effects channel suggests that the information effect plays a dominant role; CSR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 70 publications
0
28
0
1
Order By: Relevance
“…United Nations Global Compact (2020), among others, promotes corporations to take concrete actions that support the society around them and report annually on the efforts. Purposively and referencing Dutordoir et al (2018), Hu et al (2019), Hu et al (2020), andWang (2017), this study scored 1 if any of the four items or all is disclosed and 0 if none disclosed. Disclosure information in the annual reports has been widely used by previous studies to investigate the extent of CSR disclosure by firms (e.g., Akbas, 2016;Akbas & Canikli 2014;Anzonwu et al, 2018;Fallan, 2016;Hackston & Milne, 1996;Khlif et al, 2015;Niskala & Pretes, 1995;Nor et al, 2016;Ofoegbu et al, 2018;Ong et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…United Nations Global Compact (2020), among others, promotes corporations to take concrete actions that support the society around them and report annually on the efforts. Purposively and referencing Dutordoir et al (2018), Hu et al (2019), Hu et al (2020), andWang (2017), this study scored 1 if any of the four items or all is disclosed and 0 if none disclosed. Disclosure information in the annual reports has been widely used by previous studies to investigate the extent of CSR disclosure by firms (e.g., Akbas, 2016;Akbas & Canikli 2014;Anzonwu et al, 2018;Fallan, 2016;Hackston & Milne, 1996;Khlif et al, 2015;Niskala & Pretes, 1995;Nor et al, 2016;Ofoegbu et al, 2018;Ong et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, there are several empirical studies examining the relationship between corporate social/environmental performance and corporate financial performance, and company benefits from the increased communication of good information [2]. Transparency and reporting indicate positive market responses to sustainability reporting [5].…”
Section: Benefits Of Sustainability Reportingmentioning
confidence: 99%
“…In these conditions, sustainability communication can help to signal the quality of the company and to lower the cost of equity, especially in competitive markets [40]. By engaging in more social and environmental programs, several top companies in some industrial sectors show that they can differentiate themselves from other companies through their sustainability efforts and opportunities [2,40].…”
Section: Benefits Of Sustainability Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…Briones et al got a similar result that there is a positive correlation between CSR and corporate innovation [ 19 ]. Hu et al pointed out that CSR is a way to deliver some information about firms’ operations [ 20 ]. Shahzad et al made an analysis of the association between CSR and environmental sustainability, and found that social responsibility practices can significantly contribute to the green innovation of firms [ 5 ].…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%